Algae-mediated processes for the treatment of antiretroviral drugs in wastewater: Prospects and challenges. (October 2021) - Reddy, Karen; Renuka, Nirmal; Kumari, Sheena; Bux, Faizal
Abstract: The prevalence of pharmaceuticals (PCs), especially antiretroviral (ARV) drugs in various aquatic ecosystems has been expansively reported, wherein wastewater treatment plants (WWTPs) are identified as the primary point source. Consequently, the occurrence, ecotoxicity and treatment of ARV drugs in WWTPs have drawn much attention in recent years. Numerous studies have shown that the widely employed activated sludge-based WWTPs are incapable of removing ARV drugs efficiently from wastewater. Recently, algae-based wastewater treatment processes have shown promising results in PCs removal from wastewater, either completely or partially, through different processes such as biosorption, bioaccumulation, and intra-/inter-cellular degradation. Algal species have also shown to tolerate high concentrations of ARV drugs than the reported concentrations in the environmental matrices. In this review, emphasis has been given on discussing the current status of the occurrence of ARV drugs in the aquatic environment and WWTPs. Besides, the current trends and future perspectives of PCs removal by algae are critically reviewed and discussed. The potential pathways and mechanisms of ARV drugs removal by algae have also been discussed. Graphical abstract: Image 1 Highlights: The global occurrence of common ARV drugs in wastewater treatment plants observed. Ecotoxicological studies showed high tolerance potential of algae to ARV drugs. Various algal species showed high potential for PCs removal from aqueous environment. The proposed mechanisms of algae-mediated ARV drugs removal are elucidated. The fate of ARV drugs and transformation products in algal remediation needs to be explored.